Preparation and preliminary clinical application of 3D printed porous tantalum prosthesis for reconstruction of acetabular bone defect - FAN Huaquan; WANG Fuyou; HE Rui; CHEN Xin; YANG Liu (陆军军医大学学报, 2022)
Objective To establish the preparation technology and production method of 3D printed porous tantalum prosthesis for reconstruction of acetabular bone defect and to evaluate its efficacy in preliminary clinical application. Methods Four patients with Paprosky ⅡB bone defect of the acetabulum who were going to undergo total hip arthroplasty (THA) in our center from June to December 2018 were recruited in this study according to our inclusion and exclusion criteria. Based on the personalized CT data of the patient's complete pelvis, the prosthesis for acetabular bone defect was designed by specialized 3D software and fabricated by powder bed electron beam additive manufacturing. The hip visual analog scale (VAS) score, 36-item short-form (SF-36) score and Harris score for hip joint before and after operation were compared, the postoperative complications were observed, and radiographical examination was completed at the last follow-up. Results All patients obtained good postoperative outcomes after undergoing computer-designed, personalized 3D printed porous tantalum prosthesis assisted THA to repair Paprosky ⅡB acetabular defects. During a follow-up period of 22.5±3.5 months, no surgery-related complications occurred. At the last follow-up, the Harris score was 86.2±0.3, which was significantly higher than that before operation (64.5±12.1), indicating significantly improved hip function; The VAS score was 2.5±0.7, obviously lower than that before operation (7.5±0.7); the SF-36 score was increased from 39.3±6.3 to 81.6±3.8. Compared to preoperative conditions, significant improvement was achieved in quality of life. Radiological examination showed that the implanted hip prosthesis and the 3D printed porous tantalum prosthesis for the bone defect had good stability, no radiolucent line was observed, and the acetabular bone defect was effectively reconstructed. Conclusion Our established preparation technology of personalized 3D printed porous tantalum prosthesis has demonstrated excellent effectiveness for reconstruction of acetabular bone defects in preliminary clinical application.